2022
DOI: 10.1136/bmjopen-2021-060214
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and active ingredients of social prescribing interventions targeting mental health: a systematic review

Abstract: ObjectiveThis study aims to establish the effectiveness and active ingredients of UK-based social prescribing interventions targeting mental health and well-being outcomes.DesignSystematic review adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analysies guidelines and a published protocol.Data sourcesNine databases were systematically searched up to March 2022.Eligibility criteriaSocial prescribing interventions in the UK involving adults aged ≥18 years, which reported on mental health ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 67 publications
1
29
0
2
Order By: Relevance
“…Findings from the present review and numerous SP reviews of other health outcomes23 24 26 27 29 30 33 35 36 76 81 have clearly shown that the evidence was still insufficient and scientifically inconclusive to justify the recommendation reliably. Some immediate increases in physical activity and energy expenditure are noted in our study, but whether the benefits sustain post-trial is questionable.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Findings from the present review and numerous SP reviews of other health outcomes23 24 26 27 29 30 33 35 36 76 81 have clearly shown that the evidence was still insufficient and scientifically inconclusive to justify the recommendation reliably. Some immediate increases in physical activity and energy expenditure are noted in our study, but whether the benefits sustain post-trial is questionable.…”
Section: Discussionmentioning
confidence: 68%
“…A key strength of this systematic review is that it provides the first evidence of SP in addressing the determinants of chronic diseases by comprehensively synthesising the available data and applying the methodologically rigorous standards of conduct and reporting. It is recommended that this study should be interpreted together with other prior reviews to understand the impact of SP on the person (ie, physical, mental and social well-being), community groups and the healthcare system 23–36. A further strength was performing meta-analyses separately at two assessment points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social prescribing is being proposed as a solution to poor social health, as an innovative holistic community-centred approach [ 68 ]. There are systematic reviews demonstrating benefits of social prescribing to well-being [ 69 , 70 ] and quality of life [ 71 ]. A recent systematic review identified that while there was a lack of evidence on social prescribing for chronic disease risk factors, the few group-exercise programs that were identified had benefits for physical activity [ 68 ].…”
Section: Discussionmentioning
confidence: 99%